Application of the Character-Based Quantum Teaching Model in Improving Learning Outcomes of Integral Material for Class XII MIPA 5 Semester 2 SMAN 1 Tanjung Academic Year 2015/2016 - Winarno (PT FORMOSA CENDEKIA GLOBAL, 2022)
The formulation of the problem in this study is whether through the application of a character-based quantum teaching model can improve learning outcomes, namely independence, skills, and student achievement in learning mathematics integral material in class XII.MIPA.5 semester 2 of SMAN 1 Tanjung academic year 2015/ 2016?. This research was carried out in two cycles of PTK with the activities of each cycle including planning, implementing, observing, and reflecting. The research data uses primary and secondary data with test techniques in the form of descriptive tests and non-test techniques in the form of observing students' independence and skills. The analysis used a comparative description to compare the initial value and the results achieved with the classical target of 85%. Learning outcomes increased from cycle 1 to cycle 2 successively independence 70.59% to 100%, skills 64.71% to 100% and learning achievement 67.65% to 97.06% or each increased by 29 .41%, 35.29%, and 29.41%.